Vancomycin-Induced Modulation of Gram-Positive Gut Bacteria and Metabolites Remediates Insulin Resistance in iNOS Knockout Mice - Aggarwal, Hobby; Pathak, Priya; Singh, Vishal; Kumar, Yashwant; Shankar, Manoharan; Das, Bhabatosh; Jagavelu, Kumaravelu; Dikshit, Madhu (Frontiers in Cellular and Infection Microbiology, 2022)
The role of oxidative and nitrosative stress has been implied in both physiology and pathophysiology of metabolic disorders. Inducible nitric oxide synthase (iNOS) has emerged as a crucial regulator of host metabolism and gut microbiota activity. The present study examines the role of the gut microbiome in determining host metabolic functions in the absence of iNOS. Insulin resistant and dyslipidemic iNOS-/- mice displayed reduced microbial diversity, with a higher relative abundance of Allobaculum and Bifidobacterium, the gram-positive bacteria, and altered serum metabolites along with the metabolic dysregulation. Vancomycin, which largely depletes gram-positive bacteria, reversed the insulin resistance (IR), dyslipidemia, and related metabolic anomalies in iNOS-/- mice. Such improvements in the metabolic markers were accompanied by alterations in the expression of genes involved in fatty acid synthesis in liver and adipose tissue, lipid uptake in adipose tissue and lipid efflux in the liver and intestine tissue. Rescue of IR in vancomycin treated iNOS-/- mice was accompanied with the changes in select serum metabolites such as 10-hydroxydecanoate, indole-3-ethanol, allantoin, hippurate, sebacic acid, aminoadipate, and ophthalmate, along with improvement in phosphatidylethanolamine to phosphatidylcholine (PE/PC) ratio. In the present study, we demonstrate, vancomycin-mediated depletion of gram-positive bacteria in iNOS-/- mice reversed the metabolic perturbations, dyslipidemia and insulin resistance.